Distance of Recurrent Laryngeal Nerve in Relation to Superior Parathyroid Gland During Thyroid Surgery - Shrestha, Diva; Regmi, Deepak; Shrestha, Sangita; Bista, Meera (Journal of Nepal Health Research Council, 2021)
Background: In thyroid surgery, it is essential to identify and preserve recurrent laryngeal nerve to avoid injury to the nerve which will lead to nerve paralysis or paresis. The meticulous dissection of recurrent laryngeal nerve is important for careful identification and preservation of the nerve to prevent post operative vocal cord paresis and hoarseness. Methods: A single centre prospective, cross sectional study was conducted from May 2019 to January 2021 in Department of ENT and Head and Neck surgery in Kathmandu Medical College Teaching Hospital. The data on distance between recurrent laryngeal nerve and superior parathyroid gland during thyroidectomy were collected.Results: The mean distance of recurrent laryngeal nerve in relation to superior parathyroid gland during thyroid surgery was 5.03±1.79 millimeters. The recurrent laryngeal nerve lies within 5mm of superior parathyroid gland in 83.05% cases and between 6 and 10mm in 15.25 % of cases.Conclusions: The recurrent laryngeal nerve is found in the close proximity to the superior parathyroid gland. The visual method of identification of recurrent laryngeal nerve can be widely adopted in thyroid surgery to prevent recurrent laryngeal nerve injury. Keywords: Anatomical location; recurrent laryngeal nerve; thyroid surgery